2014
DOI: 10.1080/14786419.2014.926354
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoid-freeCannabis sativaL. grown in the Po valley: evaluation of fatty acid profile, antioxidant capacity and metabolic content

Abstract: Within a project aimed to reintroduce non-drug hemp cultivars in the Italian Po valley, for fibre but also high added-value nutraceutical production, investigation on locally grown plants has been performed, in order to assess their oil and metabolic content. This study provides useful information regarding three different hemp cultivars, from two sites, in view of their potential industrial application. The oil was characterised by a high unsaturated/saturated fatty acid ratio and by an almost perfect balance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 15 publications
3
21
0
Order By: Relevance
“…The main phenolic compounds that have been detected in Cannabis sativa fruits, seeds, and roots are lignans, belonging to two main groups known as phenolic amides and lignanamides [40,41]. Lignans show a wide range of health-promoting properties including antioxidant, antiviral, antidiabetic, antitumorigenic, and anti-obesity activities [42].…”
Section: Resultsmentioning
confidence: 99%
“…The main phenolic compounds that have been detected in Cannabis sativa fruits, seeds, and roots are lignans, belonging to two main groups known as phenolic amides and lignanamides [40,41]. Lignans show a wide range of health-promoting properties including antioxidant, antiviral, antidiabetic, antitumorigenic, and anti-obesity activities [42].…”
Section: Resultsmentioning
confidence: 99%
“…Pollastro et al [18] reported that hemp synthesizes characteristic molecules, such as prenylated flavonoids, stilbenoid derivatives, and lignamides, which require further investigations. Other studies [19,20] reported high amounts of polyphenols in hempseed cultivars Finola, Futura, Felina, and Carmagnola (Italy) with antioxidant activity. A special role is attributed to flavonoids, acting as free-radical scavengers and chelators of metal ions.…”
Section: Introductionmentioning
confidence: 90%
“…These include the O -glycoside versions of the aglycones apigenin, luteolin, kaempferol and quercetin, as well as cannflavin A and cannflavin B, which are methylated isoprenoid flavones that are unique to Cannabis ( Figure 2 ) ( Ross et al, 2005 ). Phenolic amides and lignanamides have also been described in Cannabis fruits and roots ( Sakakibara et al, 1992 ; Lesma et al, 2014 ). The lignanamides belong to the lignan class of compounds and include cannabisin-like compounds (of the types A-, B-, C-, D-, E-, F-, and G) and grossamide ( Flores-Sanchez and Verpoorte, 2008 ).…”
Section: Hemp Phytochemicals: Their Production Pathways and Myriad Ofmentioning
confidence: 99%